2019
DOI: 10.1007/s10123-019-00072-6
|View full text |Cite
|
Sign up to set email alerts
|

Functional interaction between Cdc42 and the stress MAPK signaling pathway during the regulation of fission yeast polarized growth

Abstract: Cell polarization can be defined as the generation and maintenance of directional cellular organization. The spatial distribution and protein or lipid composition of the cell are not symmetric but organized in specialized domains which allow cells to grow and acquire a certain shape that is closely linked to their physiological function. The establishment and maintenance of polarized growth requires the coordination of diverse processes including cytoskeletal dynamics, membrane trafficking, and signaling casca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 104 publications
0
3
0
1
Order By: Relevance
“…The study showed that Sty1 activation in response to stress is sufficient to disperse GTPase activity cluster from the cell apex and terminate cell elongation. This suggests that inhibition of the SAPK pathway translates into loss of control over focused GTPase activity [ 93 ]. This offers an explanation why in the absence of Tmk3-mediated stress regulation, apical GTPase activity is maintained in T. atroviride , albeit in a highly deregulated manner.…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that Sty1 activation in response to stress is sufficient to disperse GTPase activity cluster from the cell apex and terminate cell elongation. This suggests that inhibition of the SAPK pathway translates into loss of control over focused GTPase activity [ 93 ]. This offers an explanation why in the absence of Tmk3-mediated stress regulation, apical GTPase activity is maintained in T. atroviride , albeit in a highly deregulated manner.…”
Section: Discussionmentioning
confidence: 99%
“…This activation, in turn, regulates the polar growth of cells. Furthermore, Cdc42 positively regulates the MAPK pathway through positive feedback, thereby promoting hyphal formation [66].…”
Section: Mechanism Of Regulation Of Morphogenesis Of T Reesei Via Rho...mentioning
confidence: 99%
“…Cell division cycle 42 (CDC42) is a member of the Rho GTPase family and is crucial in controlling multicellular functions including actin cytoskeletal dynamics, membrane trafficking, transcription, and cell cycle control (Duquette and Lamarche-Vane, 2014;Pérez et al, 2020). Previous studies have revealed that CDC42 is essential for meiotic maturation and might activate the PI3K pathway in mouse oocytes by regulating PTEN and PIP3 (Li et al, 2003;Na and Zernicka-Goetz, 2006).…”
Section: Cell Division Cycle 42mentioning
confidence: 99%